Chiral geometry regulates stem cell fate and activity. (November 2019) - Dong, Lingqing; Gong, Jiaxing; Wang, Yanzhong; He, Jianxiang; You, Dongqi; Zhou, Ying; Li, Qi; Liu, Yu; Cheng, Kui; Qian, Jin; Weng, Wenjian; Wang, Huiming; et al.
Abstract: Geometry sensing of cells inevitably involves cytoskeletal remodeling and the activation of biochemical signaling, which control multiple aspects of cell behaviors, such as proliferation, differentiation and migration. A variety of size-, shape- and geometry-dependent cell behaviors have been revealed, but the role of geometric chirality in regulating cellular behaviors and the underlying biophysical mechanisms remain elusive. Here, we report an intriguing mechanotransduction of stem cells on chiral geometries that human mesenchymal stem cells (hMSCs) prefer to migrate towards dextral geometry with nearly 30% relative advantage in migration speed, referred to as "chirotaxis". We also found that cell adhesion, proliferation, and differentiation of hMSCs are greatly enhanced for cells cultured on dextral geometry than those on sinistral geometry, by triggering transcription factor AP-1 complex through p38/MAPK signaling that regulates hMSCs fate and activity. We demonstrated that the cytoskeletal network consisting of transverse and radial stress fibers exhibits a strengthening/offsetting effect on dextral/sinistral geometry through focal adhesion sites, and consequently, cell's cytoskeletal contractility on the dextral geometry is nearly 80% higher. These findings highlight the importance of geometric chirality as an extracellular cue in regulating stem cell's behaviors through cell-material interactions.